By factoring using the zero product principal.
x + 1 = 9^3 + 9^2
9y^3+8=4y+18y^2
4x^3 - 12x^2 = 9x -27
Eeeep. I hate Algebra. ;c
here is link which may help you
Factor theorem - Wikipedia, the free encyclopedia
Hi Maditay,
That first one doesn't make a lot of sense. Turns out to be x = 809. What's to factor? It's linear.
The last one can be grouped to factor. Bring everything to the left side and set equal to zero.
$\displaystyle 4x^3-12x-9x+27=0$
$\displaystyle 4x^2(x-3)-9(x-3)=0$
Finish up by factoring out the common factor of (x - 3), and then use your zero product property.